MODEL SIMULASI PERUBAHAN GARIS PANTAI DUA DIMENSI - TAMRIN
Transport sediment and coastal morphology change due to wave induced current can be analyze using a numerical simulation model based on finite difference method. Using this model, the prediction of sediment transport and coastal bathymetry changes, could be obtained more accurately, this will improve the quality the accuracy of the design of coastal protection work. A number of coastal morphology change around coastal structures have been performed, and the result show that this model was capable of showing important physical phenomena that generally observed around the coastal structures being simulated. The validation of the numerical model was made by comparing some of the model results with the results obtained by other researches such as Susumu Onaka, Watanabe, Cristopher G Coutitas, et al. In general these comparisons shows a good agreement.